2021
DOI: 10.15586/aei.v49i1.30
|View full text |Cite
|
Sign up to set email alerts
|

D-dimer concentrations in acute urticaria in children

Abstract: Introduction: Urticaria is a clinical entity presenting as wheals, angioedema, or both simul-taneously. Elevated D-dimer levels were reported in the course of chronic spontaneous urticaria. Data regarding D-dimer levels in acute urticaria in children are limited. Objectives: To assess potential associations between duration of glucocorticosteroid (GCS) therapy and D-dimer concentrations in children with acute urticaria. Patients, materials, and methods: Hospital records of 106 children (59 females), aged 5.57 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…D-dimers are a fibrin degradation products formed by activation of the clotting cascade of blood and thrombin. Previously, elevated D-dimer levels have been found in patients with AU, including those requiring prolonged corticosteroid therapy [34]. According to Zhang et al in AU there is an association of elevated D-dimers with the severity of skin lesions, moreover, high IgE levels may promote activation of the coagulation system in an extrinsic mechanism [35].…”
Section: Discussionmentioning
confidence: 99%
“…D-dimers are a fibrin degradation products formed by activation of the clotting cascade of blood and thrombin. Previously, elevated D-dimer levels have been found in patients with AU, including those requiring prolonged corticosteroid therapy [34]. According to Zhang et al in AU there is an association of elevated D-dimers with the severity of skin lesions, moreover, high IgE levels may promote activation of the coagulation system in an extrinsic mechanism [35].…”
Section: Discussionmentioning
confidence: 99%
“…Cases of urticaria in COVID-19 have also been reported [18]. The development of AU may also be associated with bacterial infections (Streptococcus, Staphylococcus, Mycoplasma pneumoniae, Chlamydia pneumoniae, Helicobacter pylori) and in a small percentage with parasitic infestations (Ascaris lumbricoides, Giardia lamblia, Anisakis simplex, Toxocara canis, Echinococcus granulosus, Strongyloides stercoralis) [11,15,17].…”
Section: Etiology Of Acute Urticariamentioning
confidence: 98%
“…Infections most commonly involve the upper respiratory tract and gastrointestinal tract, less commonly the lower respiratory tract or urinary tract [15,16]. Viral infections, including those caused by adenoviruses, enteroviruses, RSV, cytomegalovirus (CMV), Epstein-Barr virus (EBV), herpes simplex virus, influenza and parainfluenza viruses, are the most common etiologic agents [15,17]. Cases of urticaria in COVID-19 have also been reported [18].…”
Section: Etiology Of Acute Urticariamentioning
confidence: 99%
See 1 more Smart Citation
“…Zaryczański et al. found that children with AU who had higher D‐dimer levels required prolonged glucocorticoid (GC) treatment 6 . Some small‐scale case reports have shown that AU seems to be more correlated with elevated plasma D‐dimer levels than CU 7 .…”
Section: Introductionmentioning
confidence: 99%